Widths of the anisotropic Besov classes of periodic functions of several variables - Myronyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the exact-order estimates of Kolmogorov and orthoprojective widths of anisotropic Besov classes of periodic functions of several variables in the spaces L_q.